Databases, indices and structure-related queries - Ihlenfeldt, Wolf-Dietrich (Henry Stewart Talks, 2011)
Techniques to manage large structure and reaction collections, Indices, Structure keys and hashcodes, Structure and reaction fingerprints, Query rewriting, Similarity measures, Similarity indices